The Legal Regulation of Food Imports in Algeria: Protection Mechanisms and Health and Technical Standards - NOUIRI Samia (Journal of the West, 2026)
Algeria, as one of Africa's largest food importers, faces the critical challenge of balancing its significant reliance on foreign food supplies with the imperative to protect public health, support local agriculture, and ensure national food security [1]. The nation's food import bill, often exceeding USD 10 billion annually, underscores the economic and strategic importance of a robust, transparent, and effective legal framework for regulating the influx of foodstuffs [2]. This dependency, particularly in key commodities like cereals and milk where import rates can reach 75% and 50% respectively, exposes the country to global market volatility and supply chain disruptions, making the legal architecture governing imports a cornerstone of its national sovereignty and stability. Over the years, the Algerian government has navigated a complex policy landscape, oscillating between trade liberalization and protectionist measures. This has resulted in a multifaceted regulatory environment characterized by a combination of stringent safety standards, complex administrative procedures, and at times, direct import restrictions and bans [3]. The legal framework is designed not only to ensure that imported food is safe for consumption but also to serve broader economic objectives, such as reducing the trade deficit, promoting domestic production, and achieving greater agricultural self-sufficiency [4].